Knowledge about heart failure and self-care persists following outpatient programme- a prospective cohort study from the Faroe Islands. Issue 1 (1st January 2019) - Róin, Tóra; Á Lakjuni, Katrin; Kyhl, Kasper; Thomsen, Jacoba; Veyhe, Anna Sofía; Róin, Ása; Jan, Rasmussen; Marin, Strøm
ABSTRACT: Objectives : Longer life expectancies imply increased prevalence of heart failure. Blittle is known about the maintenance of disease specific knowledge following patient education. Our aim was to investigate if self-care and heart failure knowledge persists at 9 month follow up among patients with heart failure after an outpatient programme in the Faroe Islands. Methods : A prospective cohort study with patients recently diagnosed with heart failure were recruited and evaluated by questionnaire at baseline, after 3 and 9 months using The European Heart Failure Self-Care Behaviour Scale and the Dutch Heart Failure Knowledge Scale. Clinical and demographic information was collected. Results : Seven (15%) women and 40 (85%) men with heart failure and NYHA > 2 were included. There was an overall improvement in patients' self-care from baseline 25 (8) to 3 months 15 (5) and to 9 months (16 (45); both p < 0.001). Mean knowledge score 10 (3) improved to 13 (2) at 3 months and 12 (2) at 9 months (both p < 0.001). Conclusions : Disease specific patient education is applicable to heart failure patients, which can produce persistent improvements in self-care and knowledge after multidisciplinary outpatient programme. Practice Implications : Multidisciplinary outpatient programmes are beneficial for patients with heart failure and alters disease specific knowledge and self-care.